Pengaruh Kualitas Layanan (Kemudahan Donasi, Daya Tarik Kampanye, Kecepatan Respons dan Informativitas Media Sosial) terhadap Kepercayaan Donatur YBM BRILiaN - Muhamad Roozika Sunandila (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Indonesia has substantial potential in Islamic philanthropy, particularly zakat, yet its realization remains far below capacity. One of the key challenges lies in sustaining donor trust amid increasing digitalization of fundraising practices. This study aims to examine the effect of service quality dimensions, namely ease of donation, campaign attractiveness, response speed, and social media informativeness, on donor trust at YBM BRILiaN. Employing a quantitative approach, data were collected from 128 active donors using a structured questionnaire and analyzed through multiple linear regression. The results indicate that service quality simultaneously has a significant positive effect on donor trust, explaining 46.8% of its variance. Partially, ease of donation and campaign attractiveness significantly influence donor trust, while response speed and social media informativeness do not show a direct significant effect. These findings suggest that donor trust in corporate-based zakat institutions is primarily shaped by practical donation systems and persuasive campaign communication rather than by service attributes perceived as basic standards. The study provides empirical insights for zakat institutions in prioritizing service strategies that enhance donor trust and long-term fundraising sustainability in the digital era.